HUBUNGAN POLA ASUH OTORITER DENGAN KEPERCAYAAN DIRI PADA REMAJA DI KOTA MEDAN - Santi Marlina L. Tobing; Nancy Naomi G.P. Aritonang (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Self-confidence is one of the psychological aspects that helps adolescents face developmental demands, develop independence, and adapt to their social environment. Its formation cannot be separated from relational experiences within the family, including how adolescents perceive and interpret the parenting patterns applied by their parents. This study examined the relationship between perceived authoritarian parenting and self-confidence among late adolescents in Medan City using a quantitative correlational approach. A total of 350 adolescents aged 16–19 years participated as respondents, selected through purposive sampling. Data were collected using an authoritarian parenting scale based on the Parental Authority Questionnaire (PAQ) developed by Buri (1991) and a self-confidence scale based on Lauster’s (2012) aspects, followed by analysis using the Pearson Product Moment correlation test. The analysis revealed a significant negative relationship between authoritarian parenting and self-confidence (r = -0.150; p = 0.005), with the relationship strength categorized as very weak. These findings indicate that adolescents’ perceptions of more authoritarian parenting are associated with lower levels of self-confidence, although self-confidence development is also influenced by other factors beyond the variables examined in this study. The findings highlight the need for parenting approaches that integrate guidance, open communication, and support for adolescent autonomy. ABSTRAK Kepercayaan diri menjadi salah satu aspek psikologis yang berperan dalam membantu remaja menghadapi tuntutan perkembangan, membangun kemandirian, dan beradaptasi dengan lingkungan sosial. Proses pembentukannya tidak terlepas dari pengalaman relasional dalam keluarga, termasuk bagaimana remaja memaknai pola pengasuhan yang diterapkan oleh orang tua. Penelitian ini mengkaji keterkaitan antara persepsi pola asuh otoriter dengan kepercayaan diri pada remaja akhir di Kota Medan melalui pendekatan kuantitatif korelasional. Sebanyak 350 remaja berusia 16–19 tahun dilibatkan sebagai partisipan yang dipilih menggunakan teknik purposive sampling. Data penelitian diperoleh melalui skala pola asuh otoriter yang mengacu pada Parental Authority Questionnaire (PAQ) Buri (1991) dan skala kepercayaan diri berdasarkan aspek Lauster (2012), kemudian dianalisis menggunakan korelasi Pearson Product Moment. Analisis menunjukkan adanya hubungan negatif yang signifikan antara pola asuh otoriter dan kepercayaan diri (r = -0,150; p = 0,005), dengan tingkat hubungan yang tergolong sangat lemah. Temuan ini menunjukkan bahwa persepsi terhadap pengasuhan yang lebih otoriter berkaitan dengan kecenderungan rendahnya kepercayaan diri remaja, meskipun perkembangan kepercayaan diri juga dipengaruhi oleh faktor lain di luar variabel penelitian. Hasil kajian ini menegaskan perlunya pola pengasuhan yang mampu mengintegrasikan arahan, komunikasi terbuka, dan dukungan terhadap kemandirian remaja.